The relationship between advanced glycation end products, metabolic metrics, HbA1c, and diabetic nephropathy - Xue, Liping; Zhang, Yi; Zhang, Qiu (Frontiers in Endocrinology, 2025)
BackgroundIn this cross-sectional study, we aim to investigate the value of non-invasive advanced glycation end products (AGEs) detection in the early screening of diabetic nephropathy(DN) among individuals with type 2 diabetes mellitus and assess whether metabolic parameters and glycated hemoglobin A1c (HbA1c) can moderate this relationship.MethodsA total of 912 T2DM patients were enrolled. The urinary albumin-to-creatinine ratio (UACR) was measured in morning urine samples to assess DN. AGEs were non-invasively measured through skin autofluorescence. Recognizing the role of age in both AGEs and DN, AGEage was calculated as AGEs × age/100 for related analyses.ResultsThe overall prevalence of DN in the present study was 37.2%. Elevated AGEage(χ2 = 61.06) was associated with a higher prevalence of DN. Multivariable linear regression demonstrated that AGEage was positively associated with UACR levels(β = 0.154, 95% CI: 0.126, 0.306, P<0.001). In the moderation analysis, glycated hemoglobin A1c (HbA1c) affected the correlation between AGEage and UACR. Body mass index (BMI) and triglyceride glucose-body mass index (TyG-BMI) also affect the correlation between AGEage and UACR, there were significant interactions between AGEage, HbA1c, BMI, TyG-BMI, and UACR.ConclusionsComplex associations and interactions were observed between AGEs, metabolic metrics, HbA1c, and DN. Implementing comprehensive interventions can potentially benefit the prevention of DN in T2DM patients.